A STUDY OF CUBIC SPLINE INTERPOLATION. - Kai Wang (InSight: Rivier Academic Journal)
The paper is an overview of the theory of interpolation and its applications in numerical analysis. It specially focuses on cubic splines interpolation with simulations in Matlab™.